Factors Affecting Arts Marketing of Theaters in Hanoi, Vietnam - Nguyễn, Thị Anh Quyên (2023)
Arts marketing is the inevitable development trend of contemporary society, in the context of international exchanges and integration deepening and the competition in the arts field is becoming more and more intensive. If arts organizations want to successfully carry out marketing activities, they need to have a deep understanding of both theoretical and practical aspects of arts marketing. Theoretically, many researchers have pointed out that the factors impacting and affecting arts marketing include internal environment and external environment factors, in which the important factors are the external environment ones, including: Economic, political and legal factors; Cultural, social and technological factors. The objective of this study is to evaluate the influence of external environmental factors on arts marketing of theaters in Hanoi, Vietnam. The author inherits the above research points and conducts a practical survey for 50 managers and 150 artists of 12 theaters in Hanoi capital, VietnamThe important contribution of the study is shown by the author through the results of testing the scales, analyzing the correlation between the scales and testing the research hypothesis, which is: economic, political, legal factors (EPL) and Cultural, social and technological factors (CST) all have an impact on arts marketing (AM) of theaters in Hanoi, Vietnam. Moreover, Economic, political and legal factors (EPL) have a stronger influence on Arts Marketing (AM). The research results are also meaningful to many Vietnam's arts managers in planning and adjusting policies to achieve results and effectiveness in marketing activities to bring art works to the public; adapting to the market, in line with the movement and development trend of Vietnamese society and international integration.